Työaika, työllisyys ja kilpailukyky; Working Time, Employment and Competitiveness - Antti Kauhanen; Markku Lehmus (The Research Institute of the Finnish Economy (ETLA), 2019)
– This report studies working time and competitiveness. The first part of the report compares working time in Finland to other European countries using working time data from Eurostat and provides a review of the economics literature on working time and employment. The second part of the report studies the impact of the Competitiveness Pact on employment and Finnish competitiveness using Etla's macro model. This analysis separates the impact of working time extension and social security contributions and taxation on employment. The results of the working time comparison show that the average hours worked are little less than an hour shorter in Finland compared to the EU average. The low incidence of part-time work increases the average hours worked in Finland, while the working hours of both full-time and part-time employees are among the shortest in Europe. Annual holidays, public holidays and absences decrease working time in Finland more than in most other European countries. The literature review shows that the impact of working time changes on employment depend crucially on how they affect labor costs. The Competitiveness Pact increased employment and improved Finnish competitiveness. Working time extensions account for about 40% of the employment impact, while the rest is accounted for by the reductions in social security contributions and taxation.
Keywords: E24; E27; E65; J23; 330; Employment; Working time; Competitiveness; Competitiveness pact